EVALUATE THE EFFECT OF ORLISTAT, LIRAGLUTIDE, AND THE HERBAL SUPPLEMENT ON THE MOTHERS OF EXPERIMENTALLY FATTENED WHITE RATS - Zainab Hasan Majeed; Ektifa Abdul Hamid Muhammad; Muna Salah Rasheed (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The current study aimed to evaluate the effect of orlistat, liraglutide, and the herbal supplement on the mothers of experimentally fattened white rats. The female rats were divided into two main groups, the first fed a standard ration, in which two groups were the first pregnant and the second non-pregnant, while the second main group was fed a special diet containing 35%. Fat for the purpose of fattening as a first stage and for a period of 6 weeks, then the second stage began, which is the pregnancy and treatment stage and included eight secondary groups. The first group was not treated with any drug, the second group was orlistat at a therapeutic dose, the third group was liraglutide at a therapeutic dose, the fourth group was an herbal supplement, and the fifth group was a supplement with a therapeutic dose. Of Orlistat, the sixth group is supplemented with a therapeutic dose of liraglutide, the seventh group is a high dose of orlistat, and the eighth group is a high dose of liraglutide. The current study showed that the obesity leads to changes in lipid profiles compared to control groups, as the effect of fattening is represented by an increase in the concentration of total cholesterol, triglycerides, low-density lipoproteins, very low-density lipoproteins, and a decrease in high-density lipoproteins, histological examinations. Pathological changes appeared in each of the liver tissues, represented by a large proliferation of fat droplets, steatosis, Müller bodies, collapse of the central vein wall, and lymphocytic infiltration. The two best groups were when the herbal supplement was used with both drugs, and the herbal supplement had a synergistic role. With the two drugs, it reduces the accumulation of fat in the cells.